The Mediating Role of Patient Loyalty on the Relationship Between Satisfaction on Physical Environment and Intention to Recommend - Lacap, Jean Paolo (Animo Repository, 2022)
The health care industry, in general, has experienced a change in the last years due to stiff competition. More and more are now expected from hospitals, not only on offering competitive prices but also on providing quality services. With the greater expectations from patients, the need to deliver holistic quality service is a must. Hence, the present study aims to examine the level of satisfaction of patients on the aspect of the physical environment and how this satisfaction leads to the intention to recommend. Furthermore, it investigates how patient loyalty indirectly influences the relationship between satisfaction with the physical environment and intention to recommend. The respondents were selected using consecutive sampling, and they were patients from a private tertiary hospital located in Clark Freeport Zone, Philippines. Using a predictive-causal design of research and utilizing partial least squares (PLS) path modeling, the study revealed that patient satisfaction with the physical environment significantly and positively affects patient loyalty and intention to recommend. It was also found that patient loyalty leads to the intention to recommend. The mediation analysis showed that patient loyalty improves the significant and positive relationship between patient satisfaction and intention to recommend.